Incident Cerebral Microbleeds in a Cohort of Intracerebral Hemorrhage. Issue 3 (March 2016) - Pasquini, Marta; Benedictus, Marije R.; Boulouis, Grégoire; Rossi, Costanza; Dequatre-Ponchelle, Nelly; Cordonnier, Charlotte
Abstract : Background and Purpose—: We aimed to identify prognostic and associated factors of incident cerebral microbleeds (CMBs) in intracerebral hemorrhage (ICH) survivors. Methods—: Observational prospective cohort of 168 ICH survivors who underwent 1.5T magnetic resonance imaging at ICH onset and during follow-up (median scan interval, 3.4; interquartile range, 1.4–4.7) years. We used logistic regression adjusted for age, sex, and scan interval. Analyses were stratified according to the index ICH location (58 lobar ICH, 103 nonlobar ICH, excluding patients with multiple or unclassifiable ICH). Results—: Eighty-nine (53%) patients had CMBs at ICH onset, and 80 (48%) exhibited incident CMBs during follow-up. Predictors of incident CMBs at ICH onset were ≥1 CMBs (adjusted odds ratio [aOR], 2.27; 95% confidence interval [CI], 1.18–4.35), old radiological macrohemorrhage (aOR, 6.78; 95% CI, 2.76–16.68), and CMBs in mixed location (aOR, 3.73; 95% CI, 1.67–8.31). When stratifying by ICH location, incident CMBs were associated in nonlobar ICH with incident lacunes (aOR, 2.86; 95% CI, 1.04–7.85) and with the use of antiplatelet agents (aOR, 2.89; 95% CI, 1.14–7.32). In lobar ICH, incident CMBs were associated with incident radiological macrohemorrhage (aOR, 9.76; 95% CI, 1.07–88.77). Conclusions—: Prognostic and associated factors of incident CMBs differed according to the index ICH location. Whereas in lobar ICH, incident CMBs were associated with hemorrhagic biomarkers, in nonlobar ICH, ischemic burden also increased. CMBs may be interesting biomarkers to monitor in randomized trials on restarting antithrombotic drugs after ICH.